1997
DOI: 10.1103/physrevb.56.5572
|View full text |Cite
|
Sign up to set email alerts
|

Self-pumping effects and radiation linewidth of Josephson flux-flow oscillators

Abstract: Flux-flow oscillators ͑FFO's͒ are being developed for integration with a SIS mixer for use in submillimeter wave receivers. The present work contains a detailed experimental study of the dc, microwave, and noise properties of Nb-AlO x -Nb FFO's. A model based on the Josephson self-pumping effect is proposed for an explanation of the experimental current-voltage characteristics. A reliable technique based on harmonic mixing is used to determine the spectral linewidth of the radiation emitted by the integrated F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 21 publications
4
108
0
1
Order By: Relevance
“…The damping increases significantly ͑up to three times͒ for voltages above v b = 1.9 as predicted in Ref. 7. In difference with Ref.…”
Section: Including the Self-pumping Effectmentioning
confidence: 43%
See 3 more Smart Citations
“…The damping increases significantly ͑up to three times͒ for voltages above v b = 1.9 as predicted in Ref. 7. In difference with Ref.…”
Section: Including the Self-pumping Effectmentioning
confidence: 43%
“…Below v b , the IVC consists of nearly vertical, equally spaced voltage spikes, the so-called Fiske steps, which are due to electromagnetic resonances ͑Fiske resonances͒ in the JTJ. Above v b , the damping parameter is drastically increased due to the so-called self-pumping effect, 7 which is explained as a resonant tunneling of quasiparticles similar to the well-known photon-assisted tunneling ͑PAT͒. As it was shown in Ref.…”
Section: Influence Of Surface Losses On Current-voltage Charactementioning
confidence: 87%
See 2 more Smart Citations
“…The resolution, which is determined by both the instantaneous linewidth of the local oscillator and its long-time stability, should be much less than 1 ppm of the center frequency. Previous measurements of the linewidth of the FFO have demonstrated that the intrinsic linewidth increases considerably at voltages above a boundary voltage of the order of 1/3 of the gap voltage as a result of the abrupt increase of the internal damping due to Josephson self-coupling [10]. Note that the observed FFO linewidth is almost one order of magnitude wider [4,10] than predicted by the theory for a lumped Josephson tunnel junction [11,12].…”
Section: Introductionmentioning
confidence: 42%